Primary Central Nervous System Lymphoma in an Immunocompetent Young Adult Patient: A Rare Case - Aisyah Wirdah; Norman Djamaludin; Mediarty Syahrir; Yenny Dian Andayani; Mita Andriani; Yunni Diansari (Interna Publishing, 2023)
Primary CNS Lymphoma (PCNSL) is a rare form aggressive extra nodal     non-Hodgkin Lymphoma (NHL) that comprising 1-2% of the primary brain tumors that develops in the brain, spinal cord, eye or leptomeningeal area without evidence of systemic involvement. The overall incidence of PCNSL with immunocompetent patients is only 0,47/100.000 year in PCNSL. Approximately 10-20% of patients have ocular involvement and around one third have multifocal neurological disease. Overall long-term survival rate only 20-40%, this is because the management of PCNSL is limited to ability of the drug due to cross the blood brain barrier (BBB). We present a B-cell central nervous system lymphoma in an immunocompetent patient who treat responses with chemotherapy.           A 35-year-old man presented to our hospital with suddenly unconscious 4 hours before admission. He was experiencing headache and blurred of vision withing 3 months and have episode seizure. On Examination, GCS E2 M3 Aphasia, Hemiparesis dextra, papil edema, VOD/VOS: NLP. The other physical exam was normal. Laboratory tests  Hb 10,7 g/dl, LDH 446 U/L, and D-dimer 3,21ug/ml.  Rubella IgG 76,9, CMV Ig G 245,6 and, HSV IgG and IgM negative, HIV test non-reactive, Toxoplasma IgG and Toxoplasma IgM negative, HbsAg and HCV test negative. Brain MRI and MRI Spectroscopy: Lobulated mass size 7,08 cm x 4,75 cm at caudates nucleus sinistra-periventricular lateralis sinistra, Cholin/NAA ratio: 5-9, Cholin/Creatin ration 6-11 suspect malignancy dd/Lymphoma. MRI whole spine: Bulging discus intervertebral C4-C5. Chest and Abdomen CT-Scan are normal. Bone Survey normal, EEG: Epileproform left temporal. Cerebrospinal Fluid: Gliosis reaction sup malignancy.The patient underwent craniotomy and biopsy Pathology Anatomy and IHC Basal Ganglia revealed a Diffuse Large B Cell Lymphoma (NHL) Non-Germinal Center, CD 20 +, Ki 67 95% (High Grade), CD 45 +, CD 3 -, BCL6 +, Mum 1+. The patient we give induction therapy with RMP Regimens (Rituximab 375 mg/m2, day 1, 15 and 29, High Dose Methotrexate (HDMTX) 3000mg/m2 day 2, 16 and 30, and Procarbazine 60mg/m2 day 3-12) because Procarbazine in not available in Palembang we change to Dacarbazine 375mg/m2 days 3,17 and 31), Dexamethasone 5mg/6 hours, and has finished  Low Dose Whole Brain Radiotherapy for consolation therapy.                                                                                        PCNSL is rare form aggressive extra nodal NHL, especially in Immunocompetent patient. In this particular case of patients High Dose Methotrexate Chemotherapy has achieved high respond especially for this patient that showed GCS E4M5V6 and recovery neurological deficit after 2 cycle chemotherapy.